California State Legislative Board Brotherhood of Locomotive Engineers Election Reccomendations (1976)
This October 1, 1976 letter from the California State Legislative Board of the Brotherhood of Locomotive Engineers announces its endorsements for the November 2, 1976 general election. The union recommends Democratic candidates for U.S. Senate, U.S. House, State Senate, and State Assembly across California, with incumbents marked by an asterisk. Among those endorsed is Jane McCormick Tolmach (D) for the 36th Assembly District. The document reflects organized labor's broad support for Democratic candidates in that election cycle.